Polyester fabric modified with atmospheric dielectric barrier discharge supplied with voltage of different frequencies - Píchal, J.; Sláma, J. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
Final characteristics of polymers are the compromise between wanted surface and bulk properties. Important change of the polymer use-value can be caused by modification of characteristics of its upper structural units (i.e. in region under the surface deep some tens of nanometers). These changes – and modification – can be performed i. a. by treatment with the “cold” plasma and moreover with low costs and minimum environmental impact. Modification of polymer surface characteristics may proceed during functionalization, when plasma particles react with polymer surface molecules and new chemical functional groups are formed on polymer surface. These chemical reactions can be influenced with composition of atmosphere in the plasma reactor, e.g. application of oxygen plasma leads to polymer surface energy and wettability increase. To evaluate the efficiency of this process, we studied connection of the ADBD supply energy/voltage frequency and changes of the polymer surface chemical composition. ADBD was operated in the filamentary regime. Experiments proved that growing supply voltage frequency that produced also reactor input energy increase allowed both substantial reduction of treatment time and more effective modification. Конечные свойства полимеров являются компромиссом между желаемыми поверхностными и глубинными характеристиками. Существенное изменение потребительских свойств полимеров может быть вызвано модификацией характеристик его приповерхностных структурных слоев (т.е. на глубине нескольких десятков нанометров поверхностного слоя). Такая модификация может быть реализована с помощью облучения «холодной» плазмой без дополнительных затрат и минимального влияния на окружающую среду. Модификация поверхностных характеристик полимера может происходить во время обработки, когда компоненты плазмы взаимодействуют с молекулами поверхности полимера, при этом на поверхности полимера образуются новые химические группы. Эти химические реакции могут зависеть от состава газа в плазменном реакторе. Например, применение кислородной плазмы приводит к увеличению прочности поверхности полимера и ее смачиваемости. Чтобы оценить эффективность данного процесса, изучалась зависимость изменения химического состава поверхности полимера от параметров атмосферного диэлектрического газового разряда (ADBD). Эксперименты подтвердили, что увеличение питающей частоты разряда, а также входной энергии реактора приводит к существенному сокращению времени облучения и более эффективной модификации. Кінцеві властивості полімерів є компромісом між бажаними поверхневими і глибинними характеристиками. Істотна зміна споживчих властивостей полімерів може бути викликана модифікацією характеристик його приповерхневих структурних шарів (тобто на глибині декількох десятків нанометрів поверхневого шару). Така модифікація може бути реалізована за допомогою опромінення «холодною» плазмою без додаткових витрат і мінімального впливу на навколишнє середовище. Модифікація поверхневих характеристик полімеру може відбуватися під час обробки, коли компоненти плазми взаємодіють з молекулами поверхні полімеру, при цьому на поверхні полімеру утворюються нові хімічні групи. Ці хімічні реакції можуть залежати від складу газу в плазмовому реакторі. Наприклад, застосування кисневої плазми призводить до збільшення міцності поверхні полімеру і її змочуваності. Щоб оцінити ефективність даного процесу, вивчалася залежність зміни хімічного складу поверхні полімеру від параметрів атмосферного діелектричного газового розряду (ADBD). Експерименти підтвердили, що збільшення живильної частоти розряду, а також вхідної енергії реактора призводить до істотного скорочення часу опромінення і більш ефективної модифікації.